AUDIT MANAJEMEN PADA FUNGSI SUMBER DAYA MANUSIA (Studi pada Fungsi Pengembangan Organisasi, Rekrutmen-Seleksi-Orientasi, Pelatihan&Pengembangan Sumber Daya Manusia, dan Penilaian Kinerja Departemen Pengembangan Sumber Daya Manusia PT.XXX) - Anissa Barida Adni (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
This study describes about management audit of human resource function that conducted in human resource development department at PT.XXX include organizational development function, recruitment-selection-orientation function, training and developing of human resource function, and performance appraisal function. Research method that used for this study is the descriptive research using a qualitative approach. Data collection methods that been used for this study are observation, interviews, questionnaires, documentation, and literature review. The findings of this study showing that overall activities of the human resource function accordance with standard operating procedure (SOP) that applied in this company.Yet there are some items that need to be noted which mainly related with training and development of human resource is not optimal yet. Some recommendations that can be provided based on audit are socialization of the program as well as an evaluation of the socialization of the program itself, procurement, recruitment, partnership whit third-party organization, oversight and monitoring of the program execution, improvement of form that used for training and development function of human resource, and last but not least by using online platform as main platform for training and development function of human resource department. Keyword: Management Audit of Human Resource, Human Resource FunctionAbstrak Penelitian ini menjelaskan tentang audit manajemen pada fungsi sumber daya manusia yang dilaksanakan di departemen pengembangan sumber daya manusia PT.XXX meliputi fungsi pengembangan organisasi, fungsi rekrutmen-seleksi-orientasi, fungsi pelatihan&pengembangan sumber daya manusia, dan fungsi penilaian kinerja. Jenis penelitian ini adalah penelitian deskriptif dengan menggunakan pendekatan kualitatif. Metode pengumpulan data yang digunakan adalah observasi, wawancara, kuesioner, dokumentasi, dan studi pustaka. Hasil penelitian menunjukkan bahwa secara keseluruhan aktivitas fungsi sumber daya manusia telah sesuai dengan standar operasional dan prosedur (SOP) yang berlaku. Beberapa hal yang perlu diperhatikan meliputi fungsi pelatihan dan pengembangan sumber daya manusia yang pelaksanaannya belum optimal. Rekomendasi yang diberikan berdasarkan temuan audit adalah sosialiasi terhadap program serta evaluasi atas sosialisasi tersebut, pengadaan kerjasama rekrutmen dengan pihak ketiga, pengawasan dan pemonitoran terhadap pelaksanaan orientasi, perbaikan formulir pada fungsi pelatihan dan pengembangan sumber daya manusia, serta mengubah sistem pada fungsi pelatihan dan pengembangan sumber daya manusia menjadi sistem online. Kata Kunci: Audit Manajemen Sumber Daya Manusia, Fungsi Sumber Daya Manusia